Genome-wide diversity in lowland and highland maize landraces from southern South America: population genetics insights to assist conservation - Dominguez, Pia Guadalupe; Gutierrez, Ángela Verónica; Fass, Monica Irinia; Filippi, Carla Valeria; Vera, Pablo; Puebla, Andrea; Defacio, Raquel Alicia; Paniego, Norma Beatriz; Lia, Veronica Viviana (BioRxiv, 2024)
Maize (Zea mays ssp. mays L.) landraces are traditional American crops with high genetic variability that conform a source of original alleles for conventional maize breeding. Northern Argentina, one the southernmost regions of traditional maize cultivation in the Americas, harbours around 57 races traditionally grown in two regions with contrasting environmental conditions, namely the Andean mountains in the Northwest and the tropical grasslands and Atlantic Forest in the Northeast. These races encounter diverse threats to their genetic diversity and persistence in their regions of origin, with climate change standing out as one of the major challenges. In this work, we use genome-wide SNPs derived from ddRADseq to study the genetic diversity of individuals representing the five groups previously described for this area. This allowed us to distinguish two clearly differentiated gene pools, the Highland Northwestern maize (HNWA) and the Floury Northeastern maize (FNEA). Subsequently, we employed Essential Biodiversity Variables at the genetic level, as proposed by the Group on Earth Observations Biodiversity Observation Network (GEO BON), to evaluate the conservation status of these two groups. This assessment encompassed genetic diversity (Pi), inbreeding coefficient (F), and effective population size (Ne). FNEA showed low Ne values and high F values, while HNWA showed low Ne values and low Pi values, indicating that further genetic erosion is imminent for these landraces. Outlier detection methods allowed identification of putative adaptive genomic regions, consistent with previously reported flowering-time loci and chromosomal regions displaying introgression from the teosinte Zea mays ssp. mexicana. Finally, species distribution models were obtained for two future climate scenarios, showing a notable reduction in the potential planting area of HNWA and a shift in the cultivation areas of FNEA. Taken together, these results suggest that maize landraces from Northern Argentina may not be able to cope with climate change. Therefore, active conservation policies are advisable.